Integration of the STEAM-Dilemma Model (Science, Technology, Engineering, Art, and Mathematics) to Develop Collaborative and Critical Thinking Skills of Elementary School Students - Talitha Erinna; Yolanda Devi; Indri Murnilasari; Nisrina Tsabitah; Yuli Rahmawati (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2022)
This research aims to analyze elementary students' ability in critical thinking and collaborative skills by applying dilemma STEAM as an innovation of learning model which is an integration of dilemma stories and STEAM PjBL (Science, Technology, Engineering, Art, and Mathematics Project Based Learning) on sience subject in six grade elementary school in Bekasi. The method used in this research is qualitative method with observation and interviews as data collection method. Obtained data are analyzed by data reduction, data presentation, and conclusion. This research involves three teachers and 80 six grade students. Collaborative skill aspects are teamwork and being responsible in finishing the given project. Whereas, critical thinking aspects include interpretation, analysis, evaluation, and inference in constructing knowledge to finish the given project. At the end, this model is expected to be applicable to create a meaningful learning and able to develop students' competencies.